The Essence Of The Effective Leadership Model In Educational Institutions - Nurhajati, Nurhajati; Agustinus, Agustinus; Sari, Eliana; Karnati, Neti (Annpublisher, 2024)
This study elaborates on the essence of the effective leadership model in educational institutions. This research method uses a literature study method by observing various documents from books and journals. The literature study in this study focuses on researching literature related to effective leadership. Data collection is carried out by collecting literature data, reading, recording, and managing research results objectively, systematically, analytically, and critically by looking at the year of publication and the most up-to-date research. The result of this study is that effective leadership focuses on leaders of educational institutions always being target-oriented by building a humanist system and a sound control system. In addition, this leadership is also closely related to how a leader can develop his character so that he or she becomes authentic because effective and authentic leadership has a strong correlation. Compelling and authentic leadership are two elements that cannot be separated, so it is necessary to pay attention to the leaders of educational institutions when using this leadership model.